Material Database Syndication with RSS - Toshihiro Ashino (Data Science Journal, 2007)
Every material database on the Internet has a different data schema. There are some trial attempts to define unified schema for material databases, but since the structure of scientific data is very complicated and changes dynamically, defining a complete data schema is an impossible task. There are two major approaches for material data standards: one is MatDB, an attempt to define precise and detailed metadata, and the other is MatML, which only defines a framework. However, there is a third way: loose syndication, such as blogs with RSS. RSS, RDF Site Summary, or Really Simple Syndication, was developed to summarize document pages, but it can be extended to describe metadata of factual databases. In this presentation, an RSS extension for material database summaries is discussed.